2007
DOI: 10.1002/jor.20464
|View full text |Cite
|
Sign up to set email alerts
|

The growth differentiation factor 5 (GDF5) core promoter polymorphism is not associated with knee osteoarthritis in the greek population

Abstract: Genetic factors have been shown to play an important role in the etiology of osteoarthritis (OA). A functional single nucleotide polymorphism (SNP) þ104T/C; rs143383 in the 5 0 UTR of the GDF5 gene was recently associated with susceptibility to osteoarthritis in the Japanese and Chinese population. Our objective was to assess whether this SNP was also associated with knee OA in a Greek Caucasian population sample. The þ104T/C SNP was genotyped in a total of 519 case-control cohort; 251 patients with idiopathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 26 publications
4
35
0
2
Order By: Relevance
“…Our data have shown that polymorphism exist in the GDf-5 (BsiE1) gene in North Indian population. The frequency of T allele in our population (55%) was similar to that reported in Caucasians (59-63 %) (Rouault et al, 2010;Southam et al, 2007;Tsezou et al, 2008;Valdes and Spector, 2009) the oriental population carry relatively higher frequency (70-74%) of variant T allele (Shin et al, 2012;Cao et al, 2010;Dai et al, 2008;Miyamoto et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our data have shown that polymorphism exist in the GDf-5 (BsiE1) gene in North Indian population. The frequency of T allele in our population (55%) was similar to that reported in Caucasians (59-63 %) (Rouault et al, 2010;Southam et al, 2007;Tsezou et al, 2008;Valdes and Spector, 2009) the oriental population carry relatively higher frequency (70-74%) of variant T allele (Shin et al, 2012;Cao et al, 2010;Dai et al, 2008;Miyamoto et al, 2007).…”
Section: Discussionsupporting
confidence: 87%
“…Stratification of subjects on bases of sex further showed significant association of variant T allele with KOA in males and females. Similar association of variant T alleles with KOA in males and females has been demonstrated in Caucasians and Koreans (Cao et al, 2010;Tsezou et al, 2008;Southam et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our results were consistent with the results of the study performed by Tsuzou et al (17), which conformed to the heterogeneous nature of OA genetic susceptibility. Tsuzou et al (17) indicated that there were no statistically significant differences in the genotype and allele frequencies of the +104T/C SNP of the GDF5 gene in patients and controls (p>0.05).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, on categorizing the cases based on gender, no allele or genotype differences were found in the frequency distribution based on gender. Therefore, the results of the study performed by Tsezou et al (17) indicated that GDF5 (+104T/C) SNP is not a risk factor for KOA in Greek Caucasians. Similarly, our results were in accordance with the results of the study conducted by Southam et al (6), which revealed the absence of significant differences in genotype and allele frequency distribution of SNP in cases and healthy control subjects (p>0.05 and p=0.436, respectively).…”
Section: Discussionmentioning
confidence: 90%